Physicians’ perception towards continuing professional development in government teaching hospitals of Addis Ababa, Ethiopia-mixed method design - Merahi Kefyalew Merahi; Walelegn Worku Yallew (BMC Health Services Research)
Abstract Background Continuing professional development has been mandatory for healthcare professionals to renew their licenses. However, there is a shortage of information regarding physicians' perceptions of continuing professional development. Therefore, it is timely to assess the perception of physicians and barriers toward continuing professional development. Methods An institution-based quantitative design triangulated with a qualitative research design was conducted. A total of 367 and 6 study participants were included in the quantitative and qualitative study, respectively. Simple random and purposive sampling strategies were employed to select participants for the quantitative and qualitative parts. Quantitative Data was inserted in EPI-INFO version 7 and cleaned and analyzed using the Statistical Package for the Social Sciences,version 25 statistical program. Binary-dependent categorical variables were analyzed using binary logistic regression. Multiple logistic regression analysis was assessed to observe the association between perception and various explanatory variables. Thematic content analysis was conducted to develop items from transcribed qualitative information. Result This study involved 367 participants from three government teaching hospitals in Addis Ababa, Ethiopia. Being younger (20–30) had significantly higher odds of positively perceiving continuing professional development. It also showed that the department of healthcare Professionals had a statistically significant association with the perception of continuing professional development. Those working in Internal Medicine and Obstetrics and Gynecology departments and healthcare professionals had significantly higher odds of perceiving continuing professional development as good. The interviews revealed that the barriers to continuing professional development are divided into Individual and health system barriers. The Individual barriers include awareness gap, Motivation Issues and Family size, whereas the health system-related barriers include recognition, infrastructure, time, place, and accessibility. Conclusion and recommendation The study identified the department of the healthcare professional as significantly associated with perception of continuing professional development. Improving patient care collaboration and career progression influenced physicians' perception of continuing professional development. The study findings suggest the need for effective strategies to enhance physicians’ engagement in continuing professional development and improve the quality of healthcare services in Ethiopia.